Estudio de prefactibilidad para la instalación de una planta productora de suplementos alimenticios en polvo a base de cereales andinos - Cevallos Navarro, Alvaro Sebastian (2023)
The purpose of this research is to investigate the feasibility of implementing a plant for the production of powdered food supplements derived from Andean cereals and destined for the Metropolitan Lima region. In this context, the project began by consolidating the idea of elaborating food supplements based on Andean cereals, basing it economically, technically and socially. In addition, the objectives and hypotheses that will serve as the basis for this research were outlined. Subsequently, the main characteristics of the proposed product and the standards to be followed for its integration into the Peruvian market were detailed. It is essential to point out that, at the same time, the entry strategies to be followed were specified, in order to quickly consolidate the brand with the end customer. The latter, in line with the idea of reaching a significant market share percentage that will allow achieving encouraging margins. Additionally, a market study was carried out, based on the collection of first and second-hand information to justify the subject under analysis. In this way, the expected demand of the company was determined throughout its initial proposed duration of five years. Finally, in the research work analyzed, a recommendation was made for the optimal location of the production plant based on an analysis of the conditions of alternative locations using the factor ranking method. In particular, this decision is expected to result in reduced fixed costs and improved service levels.